Concordance of Parent- and Child-Reported Physical Abuse Following Child Protective Services Investigation. (February 2017) - Kobulsky, Julia M.; Kepple, Nancy Jo; Holmes, Megan R.; Hussey, David L.
Knowledge about the concordance of parent- and child-reported child physical abuse is scarce, leaving researchers and practitioners with little guidance on the implications of selecting either informant. Drawing from a 2008–2009 sample of 11- to 17-year-olds ( N = 636) from Wave 1 of the second National Survey of Child and Adolescent Well-Being, this study first examined parent–child concordance in physical abuse reporting (Parent–Child Conflict Tactic Scale). Second, it applied multivariate regression analysis to relate parent–child agreement in physical abuse to parent-reported (Child Behavior Checklist) and child-reported (Youth Self Report) child behavioral problems. Results indicate low parent–child concordance of physical abuse (κ = .145). Coreporting of physical abuse was related to clinical-level parent-reported externalizing problems (y ̄ = 64.57), whereas child-only reports of physical abuse were the only agreement category related to child-reported internalizing problems ( B = 4.17, p < .001). Attribution bias theory may further understanding of reporting concordance and its implications.